Hysterical Sustenance: A Painted Investigation into Nature and Artiface, Food and Still Life. - Brownell, Mia (2005)
Results from sabbatical resulted in grants, peer review and extensive exhibitions. Several paintings were done examining the traditions of food as a subject in still life using genetically modified food.
Keywords: dept.art; faculty_collection; sabbatical_report